From the campfire to the holodeck : creating engaging and powerful 21st century learning environments - Thornburg, David, 1943- (Jossey-Bass, 2014)
"How to optimize educational spaces, both physical and virtual, for more effective learningThe design of classroom spaces is one of the overlooked issues in education. Poorly designed physical environments can impede learning, while well-designed spaces can enhance it. From the Campfire to the Holodeck gives teachers and administrators concrete advice and insight on redesigning or optimizing educational spaces to improve student engagement, enable project-based learning, incorporate technology into the classroom, and encourage student-led learning.Author David Thornburg argues that in order to engage all students, facilities should offer a balance of Campfire spaces (home of the lecture), Watering Holes (home to conversations between peers), Caves (places for quiet reflection), and Life (places where students can apply what they've learned). From the Campfire to the Holodeck offers practical guidance on designing these beneficial spaces for optimal learning. Addresses the effects of physical spaces on learning, offering an overdue examination of an issue that is vitally important yet often overlooked Features specific, actionable advice appropriate for teachers and school administrators Written by award-winning futurist, author, and educational consultant David Thornburg A vitally important aspect of school reform, the design of educational spaces can mean the difference between student engagement and indifference. From the Campfire to the Holodeck offers practical guidance for maximizing the learning opportunities for any and every student"--